An In Vitro Comparison of Different Cementation Strategies on the Pull-out Strength of a Glass Fiber Post - Amaral, M.; Santini, M. F.; Wandscher, V.; Amaral, R. [UNESP]; Valandro, L. F. (Operative Dentistry Inc, 2009)
Purpose: To evaluate the effect of different strategies for post cementation on the pullout bond strength of a double-tapered glass fiber post cemented into a root canal. Materials and Methods: The root canals of 70 single-rooted bovine teeth (16 mm-length) were prepared to 9 mm using the preparation drill of a double-tapered glass fiber post system (White Post DC, FGM). Each specimen was embedded in a plastic cylinder using acrylic resin up to 3 mm. of the most coronal portion of the specimen and allocated into one of seven groups (n=10) based on strategies for cementation: Gr1-ScotchBond Multi Purpose plus (SBMP) + Relyx ARC resin cement; Gr2-Single Bond + Relyx ARC; Gr3-ED Primer + Panavia F resin cement; Gr4-SBMP + AllCem resin cement; Gr5-Relyx ARC; Gr6-Relyx Unicem resin cement; Gr7-Relyx Luting 2 glass ionomer cement. After cementation, the specimens were stored for seven days (in a humid environment at 37 degrees C) and submitted to pullout bond strength testing (the inferior part of each specimen was fixed and the fiber post was pulled out). The data (Kgf) were submitted to statistical analysis (one-way ANOVA and post-hoe Tukey tests, alpha=.05). The tested specimens were analyzed under the microscope and SEM for fracture analysis. Results: The strategy for post cementation affected the pullout retentive strength (Kgf) (p<0.0001) significantly. Gr6 (37.7 +/- 8(a) Gr1 (37.4 +/- 5.7(a)) and Gr4 (31.6 +/- 6.6(ab)) presented the highest pullout bond strengths. Gr2 (12.2 +/- 5.6(c)), Gr3 (6.5 +/- 5.2(c)) and Gr7 (5.1 +/- 2.8(c)) presented the lowest pullout bond strengths. Gr5 (24.2 +/- 7.4(b)) was similar to Gr4 and inferior to Gr6 and Gr1. Conclusion: The use of a three-step etch-&-rinse adhesive system appears to be effective. The application of other adhesive systems (single-bottle etch-&-rinse and self-etch adhesive systems) did not present high pullout strength values. The simplified self-adhesive resin cement (without adhesive application) presented good retentive performance. Further studies should be conducted.